Exploring forest owners’ intentions for public participation in forest management planning: a case study in the Czech Republic - Mohammadi, Zohreh; Kašpar, Jan; Tahri, Meryem (Frontiers in Forests and Global Change, 2025)
Participatory forest management constitutes an important pathway toward sustainable and inclusive forest governance, mediated by local social, cultural, and institutional dynamics. This study presented pioneering research that applied the theory of planned behavior (TPB) to investigate the intentions of non-state forest owners in the Czech Republic to involve the public in forest management planning. Data were obtained from 92 valid responses and analyzed using covariance-based structural equation modeling (CB-SEM). The results showed that attitudes, subjective norms, and perceived behavioral control had a positive influence on behavioral intention. However, only subjective norms had a statistically significant effect (β = 0.61, p = 0.021), while the effects of attitudes (β = 0.10, p = 0.515) and perceived behavioral control (β = 0.26, p = 0.277) were not significant. The model explained 86.31% of the variance in behavioral intention, demonstrating strong explanatory power despite the modest sample size. These findings provide preliminary evidence that social expectations from professional peers, local communities, and family networks play a dominant role in shaping forest owners’ willingness to adopt participatory planning approaches. Theoretically, this study extends the TPB framework by showing that normative influence predominates when attitudes and perceived control are already favorable, underscoring the importance of social legitimacy in structured institutional contexts. From a policy perspective, the results highlight the need to strengthen collective norms and institutional support through forest owner associations, peer learning, and transparent governance mechanisms. Such strategies can enhance social legitimacy and foster broader, more sustainable public participation in forest management planning.